Importance of English Language in Indian Media - Aliya Parveen A Mulla, (AG Volumes, 2022)
India's media has seen tremendous growth during the past two decades, surpassing all previous records. However, this extension does not always imply increased democratic involvement, as shown by the ideological content of the media, the international membership of the public sphere, and the interactive nature of publicness, all of which are indicative of a transition in the concept of the "public."